PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK BERBASIS HIGHER ORDER THINKING SKILLS PADA MATERI SKALA KELAS V SEKOLAH DASAR - Lia Adisa Nurjanah; I Nyoman Arcana; Nelly Rhosyida (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2019)
This research is purposed to develop Student’s Activity Sheet based Higher Order Thinking Skills in Skala Material for Elementary School Grade V, to investigate the feasibility product LKPD based on Professional Validator assessment, to investigate Student’s response towards LKPD product, and to investigate  the study result after learning process with developmental product LKPD. This research conducted in SD Negeri Karangmulyo with the subject of research is 18 students. The research method used is Research and Development (R&D). The results show that the LKDP product was successfully developed with a very good result based on validator matter experts, a good assessment based on validator media experts, a good assessment based on validator language experts, and good assessment based on class teacher. The Limited trial indicates a positive response from the students with a percentage of 100%. Then, the first trial in this research indicates a positive response from students with a percentage of  90,74%. The results of the student's score test after used LKDP product obtained an average of  84,94% with the KKM indicate the percentage of 100%. Therefore, developing product LKDP based on Higher Order Thinking Skills has very good quality and helped a student in learning Skala Materials for elementary school grade V.